Airtel : pricing in the cannibalisation era and transition to data - Sahay, Arvind, (SAGE Business Cases., 2018)
Airtel, a telecommunications company, experienced increased competition after the entrance of Reliance Jio in 2017. Reliance Jio offered free calls for life and competitive tariff plans to consumers and as a result Airtel saw a decline in its average revenue per user. Airtel must create a new pricing plan to protect its revenue and market share of the Indian Telecommunications industry.